Salvianolic acid B alleviates diabetic endothelial and mitochondrial dysfunction by down-regulating apoptosis and mitophagy of endothelial cells. Issue 2 (1st February 2022) - Xiang, Jie; Zhang, Chunling; Di, Tietao; Chen, Lu; Zhao, Wei; Wei, Lianggang; Zhou, Shiyong; Wu, Xueli; Wang, Gengxin; Zhang, Yun
ABSTRACT: Endothelial dysfunction is a critical mediator in the pathogenesis of vascular complications of diabetes. Herein, this study was conducted to investigate the therapeutic effects of Salvianolic acid B (Sal B) on diabetes-induced endothelial dysfunction and the underlying mechanisms. Diabetic models were established both in db/db mice and high glucose (HG)-induced human umbilical vein endothelial cells (HUVECs). Moreover, HUVECs were exposed to carbonyl cyanide m-chlorophenyl hydrazone (CCCP) to induce endothelial cell damage. Following Sal B treatment, pathological changes of thoracic aorta were investigated by hematoxylin and eosin, alcian blue (AB), elastic fiber, Masson, and reticular fiber staining. BCL2-associated X (BAX), B-cell lymphoma-2 (Bcl-2), Beclin1, Parkin and PTEN Induced Kinase 1 (Pink1) expression was detected by Western blot, immunohistochemistry, and immunofluorescence in thoracic aorta, HG- and CCCP-induced HUVECs. Cell scratch test, MitoTracker Red CMXRos staining and Flou-4 AM staining were separately presented to detect migration, mitochondrial activity and intracellular Ca 2+ in HUVECs. Our results showed that Sal B significantly ameliorated hyperlipidemia, hyperglycemia, hyperinsulinemia, and insulin resistance in db/db mice. Furthermore, it significantly alleviated diabetes-induced vascular endothelial dysfunction according to histopathology analysis. In diabetic thoracic aorta, HG- and CCCP-induced HUVECs, Sal B distinctly increased Bcl-2 expression and reduced BAX, Beclin1, Parkin and Pink1 expression, thereby protecting endothelial cells from apoptosis and mitophagy. Moreover, Sal B markedly enhanced migration, mitochondrial activity and intracellular Ca 2+ levels both in HG- and CCCP-induced HUVECs. Collectively, Sal B exhibited a potential to improve diabetes-induced endothelial and mitochondrial dysfunction through down-regulating apoptosis and mitophagy of endothelial cells. Abbreviations: DM: diabetes mellitus; T2DM: type 2 diabetes mellitus; Sal B: Salvianolic acid B; HG: high glucose; FBG: fasting blood glucose; TC: total cholesterol; TG: triglycerides; LDL-C: low-density lipoprotein cholesterol; HDL-C: high-density lipoprotein cholesterol; FINS: fasting insulin; HOMA-IR: homeostasis model assessment insulin resistance; QUICKI: quantitative insulin-sensitivity check index; H&E: hematoxylin and eosin; HUVECs: human umbilical vein endothelial cells; IHC: immunohistochemistry; CCCP: carbonyl cyanide m-chlorophenyl hydrazone; FCM: flow cytometry; CCK-8: cell counting kit-8